A Comparative Study of Mulla Sadra and Plantinga’s Views on the Issue of Evil - Masoumeh Ameri; Farida Rezaei (Comparative Theology)
In the tradition of Islamic philosophy, Mulla Sadra, one of the mystical philosophers, and in Western philosophical thought, Alvin Plantinga, a theistic philosopher, have both explored the issue of evil with distinct foundations and solutions. Mulla Sadra’s primary basis lies in the existence of essence, and his solutions adhere to the model of the non-existence of evil and its being contingently willed. Plantinga, on the other hand, seeks to demonstrate the non-contradiction of the logical issue of evil in light of God’s absolute power by using possible worlds and the relationship between human free will and divine omnipotence. These two thinkers share common ground in their belief in God as knowledgeable, powerful, and benevolent, but they differ in their approach to inherent sinfulness, defense of theodicy, and overcoming logical challenges. The objective of this study is not merely to explain and compare the intellectual foundations and solutions of Mulla Sadra and Plantinga regarding the issue of evil; rather, it aims to critically examine their premises and proposed solutions, ultimately presenting a comparative approach to resolving the issue of evil. The research methodology employed in this study is fundamentally theoretical and rational, analyzing the arguments of both philosophers and providing a comparative assessment. Keywords: Mulla Sadra, Plantinga, Good and Evil, Non-existence of Evil, Free Will Defense. IntroductionSince we have accepted the existence of God based on revelatory foundations and rational arguments, and considering that the essence of God is identical with complete existence and existence is synonymous with goodness, and that God possesses perfect attributes such as omnipotence, omniscience, and pure goodness, it is, therefore, appropriate to question and investigate the reason for the existence of evil in the world and to reflect upon it. In the Islamic domain, Mulla Sadra has endeavored to address the issue of evil in a way that does not harm religious beliefs, and in modern Christian theology, Alvin Plantinga has responded to this issue. Regarding the research background, one can refer to the article ‘A Comparative Study of Mulla Sadra’s and Plantinga’s Approaches to the Issue of Evil’ (Khademi & Abbasi Kia, 2012), which merely explains the foundations and solutions of Mulla Sadra and Plantinga and mentions the commonalities and differences in their views. However, it does not critique and review the foundations and solutions of each. Moreover, the conclusion of the article only states that the foundations of Mulla Sadra and Plantinga can address the issue of evil, but it does not provide a comparative solution to the issue of evil by comparing their foundations and solutions. Therefore, the innovation of the present research is that in addition to explaining and comparing the views of two Muslim and Christian thinkers, it also critiques and reviews their views, and as a result, considering the totality of Mulla Sadra’s and Plantinga’s foundations and solutions, it provides a comparative answer in which no contradiction or inconsistency is seen between evils and the existence of God and His perfect attributes. Materials and MethodsThis study is the result of a comparative study of one of the theological-philosophical topics between two thinkers from the Islamic and Christian worlds, in which the views of Mulla Sadra and Plantinga on the issue of evil are compared using an analytical method. In addition, the library method has been used to collect the materials. Research FindingsMulla Sadra faced the issue of dualism, which promoted duality and polytheism. Mulla Sadra’s foundations in solving the issue of evil include the primacy of existence, belief in divine wisdom, the best possible world, God’s omnipotence, the goodness of existence, and a general perspective on the universe.Mulla Sadra’s solutions to the issue of evil include the non-existence of evil, the incidental nature of evils, the predominance of good over evil, the removal of anthropocentric views on the issue of evil, and the wisdom and purpose of the creation of beings.Perceptual evil is an issue that the theory of the non-existence of evil faces.From Plantinga’s perspective, belief in God is entirely rational and correct even without evidence or proof. He believes that a real justification for evils cannot be found, thus he tries to prove the possibility or probability of rational justification by God for the existence of evils.Plantinga’s solutions to the issue of evil include explaining possible worlds and free will defense.In some of the new terms that form the basis of Plantinga’s arguments, there are fallacies or errors, which include pervasive evil and the critique of the realization of possible worlds and not their actuality.Similarities between Mulla Sadra’s and Plantinga’s views include belief in the existence of God, the absolute and unlimited knowledge of God, and belief in God’s absolute power and benevolence.Differences between Mulla Sadra’s and Plantinga’s views include the difference in the type of approach and the predominance of a logical view of the issue of evil by Plantinga as opposed to Mulla Sadra, the inherent nature of sin and pervasive evil, and Mulla Sadra’s defense of the theory of divine justice and Plantinga’s lack of defense in this regard. Discussion of Results and ConclusionsBy comparing the foundations and solutions of Mulla Sadra and Plantinga, the following solutions can be offered for the issue of evil:Denial of the proposition “evil exists”: Based on the principles of transcendent wisdom, good is synonymous with existence, and thus evil returns to a non-existent matter.Free will defense: Plantinga’s answer is that for God to create a world in which humans freely perform moral good, it may be necessary to allow some evils to enter. Plantinga’s response focuses more on moral evils and only addresses the issue of moral evils, whereas Mulla Sadra’s answer includes both moral and natural evils.In response to Plantinga’s defense, it is argued that if God knew that by creating humans, they would commit evil acts to such an extent voluntarily, it might have been better to refrain from creating humans. To address this inconsistency, we have no choice but to go beyond the free will defense and rely on a defense based on the purpose and wisdom of human creation. This issue indicates that, at best, the free will defense is incomplete, and it is necessary to specify the possible reason for God to create humans who voluntarily commit evil to such an extent. If it is proven from the beginning that each of the evils seen in the world is compatible with the overall design of creation, no one will ever criticize the existence of evils; because evils are in harmony with the best possible system.